Penentuan Kondisi Optimum Proses Degradasi Methanil Yellow Pada Reaktor Fotokatalitik TiO2/SiO2 - Irene Praticia Irwan; Hardeli Hamzah; Hary Sanjaya (Jurnal Periodic Jurusan Kimia UNP, 2012)
Photocatalytic reactor is a device used to degrade organic pollutants. In this study, researchers used TiO2/SiO2 photocatalytic reactor to degrade dye yellow methanil 20 ppm. This study aims to determine the number of columns used glasses and long irradiation optimum TiO2/SiO2 photocatalytic reactor to degrade methanil yellow dye. In this study, the used TiO2 Degussa P-25 with the addition of SiO2 which aims to reduce pore size and extend catalyst surface thereby optimizing the photocatalytic activity of TiO2 films. Variations in the amount of glass columns used were 3, 5, 7, 9, and 11 columns. While the variation of irradiation time is longer irradiation are 1, 2, 3, 4, 5, 6, hours. After the process of degradation, absorbance was measured using a spectrophotometer methanil yellow UV-Vis and degradation products formed at the optimum conditions were identified using GC-MS. Characterization of TiO2/SiO2 crystals using XRD. The result showed the optimum conditions methanil yellow degradation at a concentration of 20 ppm in the photocatalytic reactor that is, the number of columns as much as 9 cups of fruit and a long column of irradiation for 4 hours. In this condition, the percentage obtained by degradation of 12.63% with a flow rate of 95 ml / s and as much as 5x the amount of coating coating.